A numerical study of variability in the manufacturing process of thick composite parts. (15th January 2019) - Matveev, M.Y.; Belnoue, J.P.-H.; Nixon-Pearson, O.J.; Ivanov, D.S.; Long, A.C.; Hallett, S.R.; Jones, I.A.
Abstract: Consolidation of a prepreg layup to a target thickness is critical in order to achieve the required fibre volume fraction and dimensions in a composite part. Experiments show that different processing conditions lead to different levels of compaction and variability in the thickness. This paper presents an analysis of processing conditions and their effects on consolidation of thick composite components. A model that accounts for both percolation and squeezing flow is employed to study two toughened prepreg systems – IM7/8552 and IMA/M21. This paper analyses the significance of the process parameters on the thickness of prepregs and its variability. The analysis of different layups and processing conditions suggests several strategies to control target thickness and its variability. The IMA/M21 prepreg system was found to have lower variability due to its toughening mechanism. The presented results provide a better understanding of the composite manufacturing and can be used to provide an informed choice in design for manufacture of composite structures.